2021
DOI: 10.1016/j.ijscr.2021.106374
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative bleeding in essential thrombocytosis patients with colorectal cancer: Case report and literature review

Abstract: Introduction and importance Essential thrombocythemia (ET) is a myeloproliferative disorder characterized by increased platelet count and a high risk of bleeding or thrombotic events due to platelet dysfunction. Patients with ET are treated according to their risk of complications with cytoreductive or anti-aggregant treatment. Neither guidelines for oncologic patients nor perioperative management of patients with ET have been determined. Case presentation A 41-year-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The patient was hospitalized for 16 days and did not show any new sign of bleeding or thrombosis. 15 These findings were similar with a finding from a case series by Gurrieri et al which suggested thrombocyte count above 800,000/mm 3 was associated with an increased risk of thrombotic complications. 16 The same study suggested that operations were considered safer in patients with thrombocyte count below 450.000/mm 3 , within which 12% of patients receiving plateletpheresis had complications.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The patient was hospitalized for 16 days and did not show any new sign of bleeding or thrombosis. 15 These findings were similar with a finding from a case series by Gurrieri et al which suggested thrombocyte count above 800,000/mm 3 was associated with an increased risk of thrombotic complications. 16 The same study suggested that operations were considered safer in patients with thrombocyte count below 450.000/mm 3 , within which 12% of patients receiving plateletpheresis had complications.…”
Section: Discussionsupporting
confidence: 91%
“…The patient was given hydroxyurea 0.5 mg, agrylin 1 mg BID, and aspirin 100 mg OD, who was further admitted for operation on thrombocyte level of 920,000/mm 3 . 15 Laparoscopic was conducted without complications, but there was tachycardia with bleeding of the anterior branch of the right internal iliac artery in CT scan; hence, reoperation for embolization was performed. The patient was hospitalized for 16 days and did not show any new sign of bleeding or thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Three weeks after surgery, the patient developed anemia due to lower gastrointestinal bleeding [ 7 ]. With a therapeutic range PT-INR and stable platelet count, this event was more likely attributable to an ascending colon diverticulum than to ET or postoperative sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant advances in modern colon cancer treatments, such as surgical resection, radiotherapy, and chemotherapy, patients still need more advanced Prognosis and newer treatment strategies (Najafi et al 2021 ; Podda et al 2021 ). Surgical resection in colon cancer patients is a complex procedure with a greater risk of side effects such as pain, excessive bleeding, slow recovery, and recurrent infection (Varela et al 2021 ). Likewise, chemotherapeutic drugs adversely affect the patient’s bone marrow, hair follicles, kidneys, lungs, and nervous system.…”
Section: Introductionmentioning
confidence: 99%